Implementasi Manajemen Pembelajaran dalam Meningkatkan Motivasi Belajar Peserta Didik Kejar Paket B di PKBM Budi Utama Surabaya - Ambarliansyaputri, Ajeng Jeanrica Tri; Artha, I Ketut Atmaja Jhony (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
This study aims to study, describe, and analyze learning management in increasing the learning motivation of package B students at PKBM Budi Utama. The method in this study is qualitative descriptive. The results showed that learning management in PKBM Budi Utama consists of four stages, namely planning, organizing, implementing, and supervising. Learning planning is carried out by compiling lesson plans and teaching materials, identifying learning needs, and formulating goals. Organizing learning is done by choosing the right teaching method, learning aids according to the material, arranging the size of the class according to the number of students, and choosing the right strategy to convey the rules. The implementation of learning is carried out by strengthening the motivation of learning students and choosing strategies at all ages. Learning supervision is carried out by evaluating the learning system and measuring learning outcomes. From learning management can increase the motivation to learn learners. Proven by the encouragement and need to learn by searching the internet and taking notes, having clear hopes and aspirations for the future, getting awards from tutors, and having interesting learning activities.